THE PLACE OF ONTOGENY IN THE PROCESS OF SOCIO-ECONOMIC DEVELOPMENT - Biao, Idowu (Advances in Social Sciences Research Journal, 2016)
Abstract This paper discusses the Euro-American centric concept of development but also, a conceptual view of development which is rarely discussed in Western literature--traditional African view of development--.The paper juxtaposes the frameworks within which both the Euro-American and African concepts of development are usually operationalised and after analysing and contrasting the development operands within the two frameworks, it posits that the major differences existing among the world views, general development operands and specific development operands embedded within the two concepts, favour neither the adoption nor the imposition of the Euro-American model of development on Africa.